OPTIMALISASI PERENCANAAN PRODUKSI DENGAN PREEMPTIVE GOAL PROGRAMMING (STUDI KASUS: UD. DODOL MADE MERTA TEJAKULA, SINGARAJA) - DEVIYANTI, NI PUTU; TASTRAWATI, NI KETUT TARI; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 4 No 4 (2015), 2015)
One of the companies in production and marketing of dodol in Singaraja area is UD. Dodol Made Merta. This company produces four variants of dodol namely dodol merah, dodol kayu sugih, dodol ketan hitam, and dodol kacang. All the four dodol variants have a different demand levels.This aim of this research is to determine the optimal prediction of the amount of production that must be produced every month so that profit can be maximized by minimizing the cost of production. This research was done using two methods ARIMA. The best model for dodol merah is ARIMA ( 1,0,1), dodol kayu sugihis ARIMA(1,0,0), dodol ketan hitam is ARIMA ( 1,0,0) and dodol kacang is ARIMA(0.01).
Keywords: Time Series Stationer Model (AR, MA, ARMA); Time Series Non-Stasioner Model; ARIMA